An adenylate cyclase from Saccharomyces cerevisiae that is stimulated by RAS proteins with effector mutations. - Marshall, M S (1988)
Conservative amino acid substitutions were introduced into the proposed effector regions of both mammalian Ha-ras (residues 32 to 40) and Saccharomyces cerevisiae RAS2 (residues 39 to 47) proteins. The RAS2[Ser 42] protein had reduced biological function in the yeast S. cerevisiae. A S. cerevisiae strain with a second-site suppressor mutation, SSR2-1, was isolated which could grow on nonfermentable carbon sources when the endogenous RAS2 protein was replaced by the RAS2[Ser 42] protein. The SSR2-1 mutation was mapped to the structural gene for adenylate cyclase (CYR1), and the gene containing SSR2-1 was cloned and sequenced. SSR2-1 corresponded to a point mutation that would create an amino acid substitution of a tyrosine residue for an aspartate residue at position 1547. The SSR2-1 gene encodes an adenylate cyclase that is dependent on ras proteins for activity, but is stimulated by Ha-ras and RAS2 mutant proteins that are unable to stimulate wild-type adenylate cyclase.